2021
DOI: 10.3961/jpmph.20.540
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between General Perceptions of COVID-19 and Posttraumatic Stress Disorder in Korean Hospital Workers: Effect Modification by Previous Middle East Respiratory Syndrome Coronavirus Experience and Occupational Type

Abstract: Objectives This study investigated associations between perceptions of coronavirus disease 2019 (COVID-19) and the prevalence of posttraumatic stress disorder (PTSD) in workers at hospitals designated to treat COVID-19, as well as the difference in the magnitude of these associations by occupational type and previous Middle East respiratory syndrome coronavirus (MERS-CoV) experience. Methods The participants were workers at hospitals designated to treat COVID-19 who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Meanwhile, the COVID-19 pandemic has constantly been reported to affect people disproportionately depending on their sex, and the impact thereof on mental health is expected differ between the sexes, since women comprise higher percentages of caregivers and frontline healthcare professionals [ 12 ]. We hypothesized that upon being exposed to stress factors related to the COVID-19 pandemic, men and women would show different mental health responses, and that mental health responses would differ according to previous mental health status.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the COVID-19 pandemic has constantly been reported to affect people disproportionately depending on their sex, and the impact thereof on mental health is expected differ between the sexes, since women comprise higher percentages of caregivers and frontline healthcare professionals [ 12 ]. We hypothesized that upon being exposed to stress factors related to the COVID-19 pandemic, men and women would show different mental health responses, and that mental health responses would differ according to previous mental health status.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of our study, previous Middle East respiratory syndrome experience was associated with an increase in PTSD symptoms among hospital workers who were currently experiencing the COVID-19 pandemic [2]. In the future, when the current pandemic will come to an end, it is possible that the outbreak of a new pandemic may provoke an aggravating impact on the mental health of HCWs who have experienced the adversity of COVID-19 (possibly including non-medical personnel).…”
mentioning
confidence: 64%
“…Even taking into account the different situations of HCWs in each country, we are concerned by the current adverse experiences of medical personnel and the stigma placed on them in the Philippines. Medical professionals in many countries endure work-related difficulties caused by the pandemic, such as shortages of protective gear [1], and they also undergo stress caused by their increased workload and worries about infection, which can lead to an increased prevalence of posttraumatic stress disorder (PTSD), anxiety, and depression [2]. Nevertheless, in this urgent situation, medical professionals perceive themselves as not receiving adequate compensation or appropriate attention from their own government [3].…”
mentioning
confidence: 99%
“…They concluded that nonmedical personnel tended to have higher odds than medical personnel of being categorized as having PTSD, and those with prior Middle East respiratory syndrome coronavirus experience were more susceptible than those without such experience. These findings suggest the need for timely interventions to manage human resources for a sustainable quarantine system [1]. Another related article concluded that HCWs have a higher risk for infection than the general community, using either self-reported data on COVID-19 testing positivity or a symptombased predictor of positive infection status [2].…”
Section: Dear Editormentioning
confidence: 99%